The ecology of homicide race, place, and space in postwar Philadelphia - Schneider, Eric C. 1951-2017 (University of Pennsylvania Press, 2020)
The history of murder in Philadelphia during a critical period from World War II until the early 1980s-- Provided by publisher
Includes bibliographical references and index
Keywords: Geschichte 1940-1985; Ethnische Beziehungen; Soziale Situation; Mord; Schwarze; Philadelphia, Pa.; Homicide / Pennsylvania / Philadelphia / History / 20th century; African Americans / Pennsylvania / Philadelphia / Social conditions; Philadelphia (Pa.) / Social conditions / History / 20th century